Trabalho do pesquisador docente: análise das vivências profissionais de pesquisadores (as) de um Programa de Pós-Graduação da Região Norte do Brasil - BRASIL, Maria Clara Acacio de Oliveira (Universidade Federal do Pará, 2025)
Work makes up a considerable portion of people's time in the most diverse realities and contexts within the capitalist system in which the world is organized. Work activity defines the way a person lives, relates and accesses the world around them. Considering the weight of work, the Psychodynamics of Work theory analyzed several aspects related to this and approached work as a producer of pleasure and suffering. The aforementioned theory brought the dynamism inherent to work and exposed that the organization and conditions of work are among the determinants of the experiences lived by each worker. In this sense, the objective of the research proposed here was to analyze the experiences of a specific category of workers: researchers and university professors inserted in a Postgraduate Program in human sciences at a public university in the northern region of Brazil. The proposal takes into account the relevance of producing research work within the university environment after years of attack on the sciences, in addition to giving emphasis to researchers located in a region with the lowest social indicators in the country in terms of economic and social development, which requires a great deal of academic effort to produce quality science. The research methodology adopted was from a qualitative perspective, of the case study type, in which the methodological techniques used were: application of individual semi-structured interviews with researchers/teachers and subsequent systematization, analysis and discussion of the information collected. The analysis of the interviewees' statements was carried out using the Content Analysis technique, with the Psychodynamics of Work as its central theoretical contribution. The main results were aspects of work organization that lead to overload and extrapolation of working hours, as well as a productivist logic of work production, in addition, working conditions were found full of infrastructural deficiencies, furthermore it was evident in the research that cooperation is full of counterpoints and suffers losses due to the way the work is organized; finally, despite the impasses encountered at work, teachers demonstrated great pleasure in the recognition present in relationships with students, peers and other university workers.